PENGARUH KESEHATAN KESELAMATAN KERJA (K3) DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PT. MAJA AGUNG ELEKTRINDO TANGERANG - Melinda; Oktarini, Riri (Journal of Research and Publication Innovation, 2024)
This research aims to determine the influence of Occupationa Health and Safety (K3) and Work Discipline on the Performance of PT Maja Agung Elektrindo Tangerang Employees partiay or simultaneously. The method used in this method is a quantitative approach, the population is 57 people by taking a saturated sample or a total of 57 respondents. Data anaysis uses vaidity tests, reliability tests, classica assumption tests, regression anaysis, determination anaysis and hypothesis testing. Based on the analysis results, it was obtained that the caculated f value > f table or (9.147 > 3.17), this was aso confirmed with a significance of 0.000 < 0.05. Thus Ho3 is rejected and Ha3 is accepted, so it is concluded that Occupationa Heath (K3) (X1) on Work Discipline (X2) has a simultaneous influence on Work Performance (Y).